2020
DOI: 10.3389/fneur.2020.00084
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Long-Term Mortality and Functional Outcome After Rehabilitation in Patients With Severe Stroke

Abstract: Objective: We sought to determine sex differences in outcomes in patients with severe stroke who had been admitted to inpatient rehabilitation.Methods: We studied 1,316 patients aged 18 to 99 (mean 72) classified as case-mix groups 0108, 0109, and 0110 of the Medicare case-mix classification system. These groups encompass the most severe strokes. Three outcomes were analyzed: (1) 3-year mortality from admission to rehabilitation; (2) combined outcome of transfer to acute care or death within 90 days from admis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 50 publications
2
21
0
Order By: Relevance
“…It is not understood if gender affects prognosis after ischemic stroke. It has been reported that the proportion of patients in intensive care or who died within 90 days of anterior artery occlusion did not vary by gender [46]. Similarly, gender was not found to affect EVT benefits and outcomes [47].…”
Section: Discussionmentioning
confidence: 99%
“…It is not understood if gender affects prognosis after ischemic stroke. It has been reported that the proportion of patients in intensive care or who died within 90 days of anterior artery occlusion did not vary by gender [46]. Similarly, gender was not found to affect EVT benefits and outcomes [47].…”
Section: Discussionmentioning
confidence: 99%
“…The FIM is currently considered as the most widely used measure to describe the degree of impairment in activities of daily living in clinical practice ( 64 ). Based on Rasch analysis FIM motor scores were categorized in previous research ( 65 ) into three levels: good, fair, and poor outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The covariates examined included age (per 5-year increase), marital status (married/not married), hypertension, diabetes, COPD, history of CAD, AF, anemia, renal dysfunction, time from stroke onset to rehabilitation admission, ischemic stroke, dysphagia, neglect, and motor and cognitive FIM scores at admission. These variables were selected based on prior studies showing an association with the outcomes of interest 6,30,[42][43][44][45][46][47][48][49][50][51][52][53][54][55][56] . A multivariate logistic regression analysis with backward stepwise selection (p > 0.20 for exclusion) was performed to assess the association of covariates with 3-year mortality.…”
Section: Methodsmentioning
confidence: 99%
“…Comorbidities were defined as described in a previous study 42 . Coronary artery disease (CAD) was diagnosed based on a documented history of myocardial infarction, percutaneous coronary angioplasty, or coronary artery bypass grafting, or a previous hospitalization for CAD.…”
Section: Methodsmentioning
confidence: 99%